Occlusion of excretory ducts in experimental acute pancreatitis - Giossa, Walter; Bianchi, Gerardo; Rodríguez, Fernando; Guariglia, Roque; Pomatta, José; Lucas, Néstor; Fontan, Luis (Cirugía del Uruguay, 1986)
Comparative study of two series of 20 dogs each, in which acute pancreatítis was induced by means of direct trauma of the pancreatic parenchyma. One of the series was permilted to evolve spontaneously and the other was injected Ethibloc in pancreatic excretory ducts. Both series are compared from the point of view of biochemistry (amilacemia and glycemia) and anatomo-pathology al the time of the necropsy and also, by pancreatic biopsy, at the time ot injection ot ducts. Results obtained in the injected series are a rise in the percentage of survival and a regression in the pancreatic anatomo-pathological lesions.